STRATEGI PENGEMBANGAN KONTEN MARKETING VOKASI DALAM MENINGKATKAN AWARENESS PADA MEDIA SOSIAL INSTAGRAM @SMBTELKOM TAHUN 2023 - Yuma, Figlia Reyandha; Mustikasari, Ati (eProceedings of Applied Science, 2023)
Telkom University utilizes the social media platform Instagram for interaction and dissemination of specific information. On the Instagram account @smbtelkom, promotional content targeting prospective new students is showcased. Based on the interview results conducted with the Marketing and Analytics Division on the @smbtelkom Instagram account, apart from promotions, information about Bachelor's and Vocational programs is also provided. In addition to the Bachelor's program, there is a need for further development of the Vocational program due to decreasing insights and a lack of content discussing the Vocational program. The goal of this research is to determine the strategy of developing vocational marketing content to increase awareness on the Instagram social media platform @smbtelkom. This study employs a qualitative research approach, which involves describing the obtained data from informants descriptively using the data collection method of triangulation, including observation, interviews, and documentation. Based on the research results, vocational content marketing has successfully increased follower awareness through interactions via direct messages and comments. Although the target audience still prefers content related to bachelor's degrees, vocational content has shown positive development, as seen through increased insights in accounts reached, accounts engaged, and profile activity.Keyword: Social Media, Content Marketing, Instagram, Vocational, Awareness